Data‐driven approach to using individual cattle weights to estimate mean adult dairy cattle weight. (2nd November 2019) - Schubert, Hannah; Wood, Sarah; Reyher, Kristen; Mills, Harriet
Abstract : Background: Knowledge of accurate weights of cattle is crucial for effective dosing of individual animals and for reporting antimicrobial usage. For the first time, we provide an evidence‐based estimate of the average weight of UK dairy cattle to better inform farmers, veterinarians and the scientific community. Methods: Data were collected for 2747 lactating dairy cattle from 20 farms in the UK. Data were used to calculate a mean weight for lactating dairy cattle by breed and a UK‐specific mean weight. Trends in weight by lactation number and production level were also explored. Results: Mean weight for adult dairy cattle in this study was 617 kg (sd=85.6 kg). Mean weight varied across breeds, with a range of 466 kg (sd=56.0 kg, Jersey) to 636 kg (sd=84.1, Holsteins). When scaled to UK breed proportions, the estimated UK‐specific mean weight was 620 kg. Conclusion: This study is the first to calculate a mean weight of adult dairy cattle in the UK based on on‐farm data. Overall mean weight was higher than that most often proposed in the literature (600 kg). Evidence‐informed weights are crucial as the UK works to better monitor and report metrics to measure antimicrobial use and are useful to farmers and veterinarians to inform dosing decisions.